2015
DOI: 10.1016/j.brainres.2015.03.053
|View full text |Cite
|
Sign up to set email alerts
|

Effects of discontinuing a high-fat diet on mitochondrial proteins and 6-hydroxydopamine-induced dopamine depletion in rats

Abstract: Diet-induced obesity can increase the risk for developing age-related neurodegenerative diseases including Parkinson’s disease (PD). Increasing evidence suggests that mitochondrial and proteasomal mechanisms are involved in both insulin resistance and PD. The goal of this study was to determine whether diet intervention could influence mitochondrial or proteasomal protein expression and vulnerability to 6-Hydroxydopamine (6-OHDA)-induced nigrostriatal dopamine (DA) depletion in rats’ nigrostriatal system. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
(54 reference statements)
2
11
0
Order By: Relevance
“…The presented results also demonstrate that WD consumption for 12 weeks causes a dysregulation of the dopaminergic system in the striatum and HPC, as reflected by the decrease of DA levels in the striatum by 20% and DA turnover in the HPC by 40% in WD rats compared to controls. Our findings parallel data observed by Ma et al who also showed a decrease of DA levels and no change in DA turnover in the striatum of rats fed a 60 kcal% HFD for 13 weeks (Ma et al, 2015 ). Results by Baladi et al using chronoamperometry also indicated a decrease in DA turnover in the striatum though interestingly this was independent to any observed changes to body weight in high fat diet fed rats (Baladi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…The presented results also demonstrate that WD consumption for 12 weeks causes a dysregulation of the dopaminergic system in the striatum and HPC, as reflected by the decrease of DA levels in the striatum by 20% and DA turnover in the HPC by 40% in WD rats compared to controls. Our findings parallel data observed by Ma et al who also showed a decrease of DA levels and no change in DA turnover in the striatum of rats fed a 60 kcal% HFD for 13 weeks (Ma et al, 2015 ). Results by Baladi et al using chronoamperometry also indicated a decrease in DA turnover in the striatum though interestingly this was independent to any observed changes to body weight in high fat diet fed rats (Baladi et al, 2015 ).…”
Section: Discussionsupporting
confidence: 92%
“…Increasing evidence indicates that AMPK is a neuroprotective factor [56,57], and a high fat diet likely reduces AMPK activity in brain. Hippocampal levels of both total and phosphorylated AMPK were reduced after high fat consumption [57], and our previous study found that a high fat diet greatly reduced the phosphorylation of AMPK in rat striatum [11]. We also found lower activation of AMPK (measured by pAMPK/total AMPK) in the striatum of high fat rats, suggesting either lower cellular energy demand or suboptimal responses to cellular energy demands.…”
Section: Discussionmentioning
confidence: 60%
“…Conversely, hippocampal cognitive deficits were associated with lower serine racemase (the enzyme that synthesizes D-serine from L-serine) and D-serine concentrations in aged rats [39]. Increased serum insulin levels have been measured in aged rats [40] and in rats fed a high fat diet [10, 11], and likely accounted for the decreased Ser in the current study. The mechanism underlying this effect is unclear, however, because a high fat diet decreases insulin transport across the blood-brain barrier [41].…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations